Factors affecting public school choices among parents in Gombak district of Selangor, Malaysia - Mohamed Osman, Mariana; Bachok, Syahriah; Harun, Nor Zalina; Rabe, Noor Suzilawati; Ibrahim, Nuraihan (American Scientific Publishers, 2017)
Provision and strategic location of schools are the national educational agenda of Malaysia. Schools must follow various legislative and guidelines provision as guided by the Ministry of Education. However, there exists mismatch of number of pupils and teachers in some schools, resulting in ineffective delivery of academic curricula, less than satisfied parents, inappropriately located schools and safety or security issues. This study looks at school criteria of selection by parents and factors influencing such decision to enrol their children. Whilst academic performance record was being perceived as the most important criteria, many parents also considered school location, school distance, school facilities and extra co-curricular activities as guiding principles. Additionally, recommendations such as physical extension of schools with higher demand and improvement of teachers’ quality and school facilities were made of schools with lower demand. Easing of congestion and safety or security can be ensured by strategically locating schools near public transport nodes, supported by surveillance mechanisms.